BUSINESS AND EDUCATION: THE EVER-GROWING CHASM - Lupul, Manoly R. (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1970)
On the surface, the above subject might appear a very strange - perhaps even ridiculous - one to write about at this time. Certainly the cooperation between business and the schools has never been closer than it is at present. Business education, for example, is firmly established in all high schools and schools of business administration or commerce abound on North American campuses. The enormous growth in the 1960s of vocational education programs to accommodate the needs of business (euphemistically termed "society") also illustrates the close relationship which exists between business and the schools. And, of course, the equally close relationship between business and higher education, which observant university students have noted in recent years, is now conventional wisdom.